PERANCANGAN INTERIOR RUANG REKTORAT UNU KALTIM SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS KARYAWAN: PENDEKATAN PSIKOLOGI RUANG - Arifin, Fitriyani (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
The office has a important significant role in daily activities. The office is where various work activities are carried out, such as processing data, collecting and distributing information to achieve organizational goals. Every institution needs a well-functioning office to carry out its activities. However, the implementation of the interior design of the UNU Kaltim Rector's Office has shortcomings that are not yet able to support the needs of workers. This has impact on worker satisfaction in optimizing their performance to carry out their activities. Researchers used descriptive qualitative methods regarding spatial psychology theory. The analysis techniques used are data reduction, data presentation, and conclusions. After the research was completed, it continued by designing the interior of the UNU Kaltim rector's office using modern natural concepts and psychological aspects of space. Moreover, applying psychological aspects could improveemployee work productivity.